Development of pointing, acquisition and tracking (PAT) algorithms for inter-satellite laser (ISL) cross-links - Lian, Wei Ming. (2010)
This Final Year Project document deals with the Software Development for PAT in Inter-Satellite Laser (ISL) Cross-links to achieve line of sight laser communication between the satellites.